Indigenous soil and water conservation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Sustaining the soil: indigenous soil and water conservation in Africa edited by Chris Reij, Ian Scoones and Camilla Toumlin 1996 260pp ISBN 1 X5383 372 X published by Earthscan Publications Limited and available from CTA who are also supporting t